2013
DOI: 10.11604/pamj.2013.15.155.2341
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of Rifampicin and Streptomycin in combination against Mycobacterium ulcerans infection: a systematic review

Abstract: Buruli ulcer (BU) is a cutaneous neglected tropical disease caused by Mycobacterium ulcerans. Synthesizing the evidence on their efficacy of antibiotic in the management of BU can help to better define their roles, identify weaknesses and inform clinicians on relevant measures than can be used to control BU. Our objectives is to assess the clinical efficacy of Rifampicin-Streptomycin given for 8 weeks of treatment of early M. ulcerans infection. We searched the following electronic databases from January 2005 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Medical treatment using daily oral rifampin and intramuscular streptomycin for 8 weeks was introduced in the early 2000s (22) and is recommended by the WHO (1). A review of treatment studies performed in eight African countries and one in Australia showed that this regimen achieved on average a 50% cure rate (30). This antibiotic regimen is highly effective for lesions that are less than 10 cm in diameter, as these patients may not require surgery.…”
Section: Treatmentmentioning
confidence: 99%
“…Medical treatment using daily oral rifampin and intramuscular streptomycin for 8 weeks was introduced in the early 2000s (22) and is recommended by the WHO (1). A review of treatment studies performed in eight African countries and one in Australia showed that this regimen achieved on average a 50% cure rate (30). This antibiotic regimen is highly effective for lesions that are less than 10 cm in diameter, as these patients may not require surgery.…”
Section: Treatmentmentioning
confidence: 99%
“…11 Other investigators have also reported that oral antimicrobial therapy alone is not effective in treating BU, and surgical intervention was required in other studies. 4,7,9,12 Thus, although oral antimicrobial therapy has emerged as an attractive alternative to surgery for BU treatment, the regimen, administration, duration and efficacy of the optimal treatment remain undefined. To date, there are no published studies on the efficacies of BU treatments in Asian countries, possibly because of the much lower occurrence of reported BU cases than in endemic countries.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 122 patients, 90 were clinically cured, but 21 were referred for surgery (eight patients refused surgery and three dropped out) . Other investigators have also reported that oral antimicrobial therapy alone is not effective in treating BU, and surgical intervention was required in other studies …”
Section: Introductionmentioning
confidence: 99%
“…No systematic review of the literature on Buruli ulcer has previously been performed. A review of the efficacy of daily administration of rifampicin and streptomycin in the treatment of early‐stage Buruli ulcer including data from 2005 to 2012 was published in 2013 (Vouking 2013). In that review, evidence of diagnostic accuracy and ascertainment of cure was not clear.…”
Section: Introductionmentioning
confidence: 99%